Partnerships in maths parents and schools : the IMPACT Project - Merttens, Ruth.; Vass, Jeff. (London ; Washington, D.C. : Falmer Press, 1993)
The IMPACT Project involves individuals concerned with formal maths education and aims to bring parents and children together to share in maths activities. Each part of this book focuses on a particular aspect of parental involvement.
Book Cover; Title; Contents; Introduction; IMPACT: Pride, Prejudice and Pedagogy: One Director's Personal Story; IMPACT and the Early Years Classroom; Maths in My Home; A Probationer's Year on IMPACT'S Probationary Year; IMPACT: A Parent's Personal Perspective; IMPACT: Does It Really Make a Difference? A Teacher's Personal View; IMPACT: A Humberside Perspective; IMPACT in the Urban Authority; IMPACT: Changes in a Support Teacher's Role; Child-Centredness, IMPACT and the National Curriculum; IMPACT at the Core of the Curriculum: The Work of a Primary Maths Adviser in the New Era
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: IMPACT (Project); Mathematics -- Study and teaching -- Great Britain; Education -- Parent participation; Electronic books